Land the tech job you love - Lester, Andy (Pragmatic life., 2009)
You've got the technical chops -- the skills to get a great job doing what you love. Now it's time to get down to the business of planning your job search, focusing your time and attention on the job leads that matter, and interviewing to wow your boss-to-be.You can't just wing it.